PENETAPAN NAFKAH MANTAN ISTRI DALAM MASA IDDAH DI PENGADILAN AGAMA SUNGAI PENUH - Jaka Sandara; Ikhwan Ikhwan (UIN Imam Bonjol Padang, 2020)
As the purpose of marriage in Islam, it is not solely for outer pleasure but also forms an institution where men and women can guard themselves from error and sinful acts, give birth and care for children to continue human descent and fulfill reasonable and necessary sexual needs to create comfort and happiness. In order for the realization of a happy family the husband and wife must fulfill their obligations. One of the husband's obligations is material which is called livelihood, but in fact many families end up in divorce which results in ex-husbands having to fulfill their obligations despite divorce which is called a living, this must certainly be in accordance with Islamic law and law. applicable law, this is where judges are required to decide decisions that are fair and not detrimental to both parties, this inquiry will discuss how judges decide the case of living in the court of Religion As the purpose of marriage in Islam, not solely for outward pleasure but also establish an institution in which men and women can guard themselves from error and sinful acts, give birth and care for children to continue human descent and fulfill reasonable sexual needs and are needed to create comfort and happiness. In order for the realization of a happy family the husband and wife must fulfill their obligations. One of the husband's obligations is material which is called livelihood, but in fact many families end up in divorce which results in ex- husbands having to fulfill their obligations despite divorce which is called a living, this must certainly be in accordance with Islamic law and law. applicable law, this is where the judge is demanded to be able to decide a verdict that is fair and not detrimental to both parties, this questionnaire will discuss how the judge decides on the case of living in the religious court on a Sungai PenuhKeyword: iddah, Nafkah, Pengadilan Agama A. Pendahuluan